Impact of dental fluorosis on the oral health related quality of life among 11‐ to 14‐year‐old school children in endemic fluoride areas of Haryana (India). (1st May 2020) - Shyam, Radhey; Bhadravathi Chaluvaiah, Manjunath; Kumar, Adarsh; Pahwa, ManjuBala; Rani, Geeta; Phogat, Ritu
Abstract: Objective: This study investigates the impact of dental fluorosis on the oral health‐related quality of life (OHRQoL) among 11‐ to 14‐year‐old school children in endemic fluoride areas of Haryana (India). Materials and methods: A cross‐sectional survey was conducted among 2, 200 school children in endemic fluoride areas of Haryana. Using cluster random sampling, three districts out of 14 endemic fluoride districts were selected, and children 11–14 years of age were examined. A child perception questionnaire (CPQ11–14 ) (Hindi version) evaluated the impact of dental fluorosis on OHRQoL. The Thylstrup‐Fejerskov index (TFI) was used for assessing dental fluorosis. The data were analysed using SPSS version 18, and non‐parametric tests were used to assess the significance. The regression analysis was used to determine the effect of change in CPQ scores with dental fluorosis at P  < 0.05. Results: The study participants included 45.3% males and 54.7% females among which mild to moderate level of dental fluorosis was identified with mean mean TFI Scores being 3.19 ± 1.55. Children without dental fluorosis had 1.17 times more odd of percieving their oral health as excellent/good when compared to children with dental fluorosis ( P < 0.05). Study subjects with dental fluorosis did not have higher mean CPQ11–14 domain and total scores when compared with subjects without dental fluorosis. Conclusion: It can be concluded that mild dental fluorosis did not affect the OHRQoL of the children in the endemic fluoride areas of Haryana in India.